Effect of stress migration on electromigration for nano scale advanced interconnects - Anson Heryanto (2012)
The interconnect system is a significant part of the integrated circuit because of its function to connect millions of transistors, and routing signals into and out of the chip. Therefore, investigating its reliability is a priority for the industry to ensure that the chip lifetime will meet the requirements. In order to evaluate reliability, tests must be performed under a harsher, but nonetheless representative, environment than those expected under normal use in order to obtain failure statistics in reasonable times.